2021
DOI: 10.1038/s41598-021-00355-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of RNA extraction methods from human metabolic tissue samples of the COMET biobank

Abstract: Constitution of biobank of human tissues requires careful handling and storage of biological material, to guarantee the quality of samples. Tissue preparation is also critical for further applications such as transcriptomic profiling. In this study, our aim was to evaluate the impact of different disruption techniques (FastPrep-24 instrument, GentleMACS dissociator, and syringe/needle) and homogenizing buffers (RLT versus QIAzol) on RNA purity and quality of metabolic tissues (adipose tissues, liver and skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
2
20
2
Order By: Relevance
“…Critical variables that influenced the quality of the RNA also included the conditions of the tissue, or the impact of degradation, during processing steps. The vulnerability of RNA in rat ILMs contradicts findings that characterize skeletal muscle mRNA as highly stable relative to the liver and brain 10,11 . These evaluations suggested that variable RNA stability across species, tissue types, and organ layers may require modified extraction strategies according to the specimen and sample size.…”
Section: Introductioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Critical variables that influenced the quality of the RNA also included the conditions of the tissue, or the impact of degradation, during processing steps. The vulnerability of RNA in rat ILMs contradicts findings that characterize skeletal muscle mRNA as highly stable relative to the liver and brain 10,11 . These evaluations suggested that variable RNA stability across species, tissue types, and organ layers may require modified extraction strategies according to the specimen and sample size.…”
Section: Introductioncontrasting
confidence: 56%
“…2A). The applied RNase inhibiting reagent (RNAlater), which hinders RNase activity through precipitation and metal chelation 10 , significantly increased the RIN in the overall model (P < 0.0001, Fig. 2A, Table 1).…”
Section: Impact Of Rna Stabilizing Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…Critical variables that in uenced the quality of the RNA also included the conditions of the tissue, or the impact of degradation, during processing steps. The vulnerability of RNA in rat ILMs contradicts ndings that characterize skeletal muscle mRNA as highly stable relative to the liver and brain 10,11 .…”
Section: Introductionmentioning
confidence: 65%
“…Pathological investigation of laryngeal muscle tension disorders is particularly favorable in the rat, a well-studied model of RLN injury and vocal fold paralysis 8 . Unfortunately, ILMs have not been amenable to high-throughput assessments as readily as other soft tissue types due to technical and biological challenges 10 . The impact of these challenges on the RNA extracted from skeletal muscles, including the ILMs, is consistent across species 11 .…”
Section: Introductionmentioning
confidence: 99%